Development and Evaluation of an Aquifer Capability Screening Tool Pilot Study: Clarence-Rockland, Ontario - Morton, Samuel R. (Université d'Ottawa / University of Ottawa, 2015)
Increased development pressure led the United Counties of Prescott and Russell to seek development of a GIS-based Aquifer Capability Screening Tool (ACST). A Pilot ACST, developed by a project partner within this study, was made for the City of Clarence-Rockland, Ontario, and consists of several maps showing delineated areas where there may be groundwater limitations in terms of quality or quantity. This study gathered the chemistry data needed for the Pilot ACST from 127 domestic dug and drilled wells. The results showed exceedances of provincial health and aesthetic standards, which were then used to delineate maps for the Pilot ACST. An evaluation of the necessary data source and sampling scale for ACST development revealed that data gathered from existing reports was inadequate for various reasons and sampling scale should be on a grid 2x2 km2 or smaller. Further recommendations were provided for future ACST development studies.
Keywords: Hydrogeology; Groundwater; Geochemistry; Drinking water; Aquifer Capability Screening Tool; ACST; Municipal planning; Sampling; Mapping; ArcMap; GIS; Fluoride; Colour; Coliforms; Health Standard; Aesthetic Objective